Paula and Jerome towards a theology of Late Antique pilgrimage - Bader, Giselle (2018)
This paper examines Jerome's account of Paula's pilgrimage in 385. Written by a well-known theologian and writer, the account was intended to be read by the wider Christian world. Self-consciously didactic in nature, Jerome portrays Paula as the ideal pilgrim - ascetic, charitable, and with a strict adherence to the scriptures and Church doctrine, rather than local beliefs and practices. Jerome was cautious of pilgrimage's potential to foster the movement of heresies and its draw as a touristic, rather than spiritual, practice. Paula's depiction as the ideal pilgrim reveals the Church's desire to establish a theology of pilgrimage. Jerome did not wish to encourage the practice, but proposed that if one did embark on pilgrimage, encounters with the sacred were not attainable unless the pilgrim first possessed the ideal ascetic character and motivations. Jerome therefore sought to curate the way Christians both practised pilgrimage and subsequently read sacred landscapes.
Keywords: Bethlehem; Eustochium; Holy Land; Jerusalem; Pilgrimage; St Jerome; St Paula; fourth century